Titanium dioxide and gold nanoparticles toxicity in albino rats: Biochemical, anatomical, histopathological, and immunohistochemical studies - Yasmine A. Mansour; Alaa H. Elsayed; Fady Sayed Youssef; Sameh H. Ismail; Gehad Genidy Mohamed; Meray N. Ramsis; Samar Kamel; Basma A. Elkhadrawey; Mujtaba Farooq Rana; Heba H. Mahboub; Aya M. Mekkawy (Tissue and Cell, 2027)

Cardioprotective Effects of Spirulina platensis-Stabilized Selenium Nanoparticles: Antioxidant Enhancement and Downregulation of NLRP3 and VEGF Expression - Samah N. Badr; Mohammed A. Hussein; Elsayed H. Eltamany; Nasser Y. Mostafa; Ahmed O. Abbas (Journal of Pharmaceutical Innovation, 2027)

The interplay of bosentan and finerenone in amelioration of cardiac dysfunction within benign prostatic hyperplasia in rats - Marwa Monier Mahmoud Refaie; Asmaa A. Hasan; Asmaa A. Muhammed; Randa Ahmed Ibrahim; Eman Abdel Naby Hassan; Enas Fathy; Aml Mohamed Soliman; Hoda S. Sherkawy; Olivia N. Beshay; Amr Alam-Eldin Ahmed; Ahmed Ahmed; Samar Hisham Elsayed; et al. (Molecular Biology Reports, 2026)

Pharmaceutical Innovation in Salivary Biomarker Research: Transforming Oral Healthcare through Nanotechnology and Point-of-Care Systems: A Narrative Review - Akram N. Salah; Ahmed E. Elesawy; Mohamed Bakr Zaki; Ahmed I. Abulsoud; Gharieb S. El-Sayyad; Wagiha S. Elkalla; Nehal I. Rizk; Osama A. Mohammed; Hend H. Mohamed; Nourhan H. Elshami; Asmaa A. Ibrahim; Salma W. Elsayed; et al. (Journal of Pharmaceutical Innovation, 2026)

Dietary lemon essential oil mitigates metalaxyl-induced oxidative stress, hematological disruptions, and immunotoxicity in Nile tilapia (Oreochromis niloticus) with associated changes in splenic MAPK-and caspase-related gene expression - Elsayed M. Younis; Afaf N. Abdel Rahman; Tarek Khamis; Abdelwahab A. Abdelwarith; Simon J. Davies; Faozi S. Shamlol; Nehal A. Younis; Rowida E. Ibrahim; Gehad E. Elshopakey (Research in Veterinary Science, 2026)

L-tryptophan functionalized NH2 -UiO-66(Zr) crosslinked with glutaraldehyde adsorbent for sensitive detection and effective removal of mercury (II) - Nadia H. Elsayed; Nawaa Ali H. Alshammari; Maymounah N. Alharthi; Raedah A.S. Alatawi; Abeer Abdulaziz H. Bukhari; Ali Hamzah Alessa; Menier Al-Anazi; M.A.M. El-Afify (Journal of Water Process Engineering, 2026)

Culturomics of the plant microbiota: the emerging in situ similis cultivation strategies to meet the complexity of nutritional requirements of microbiota associated with plants of multiple species, growth stages and compartments - Nabil A. Hegazi; Sascha Patz; Florian Fricke; Ayatollah S. El-Zayat; Marwa N. Ahmed; Mervat A. Hamza; Nada A. Moner; Randa M. Abdel-Fatah; Eman H. Nour; Tarek R. Elsayed; Mahmoud S. Abdelwahab; Omar M. Shahat; et al. (Plant and Soil, 2026)
Background The holobiont" refers to the plant and its associated microbiota that are pivotal to the plant's health, fitness, and survival. By in vitro culturing and functionally characterizing members of the plant microbiota, their specific roles in influencing plant responses to environmental changes can be determined and manipulated to foster sustainable agriculture and ecosystem management. Aims The review presents a comprehensive survey and current updates on culturomics of plant microbiota within the overall context of: a) the importance of understanding the plant holobiont composition and functioning; b) the necessity to in vitro track down and explore environmental microbiomes, entailing the plant microbiome with its myriad composition and spatio-temporal dynamics and mobility in various plant species, compartments and growth stages and c) the recent developments of the emerging in-situ similis cultivation strategies grounded on plant-based culture media. Conclusions The review highlights the urgent need to explore in vitro cultivation strategies built on compatible plant-based culture media, and the transformative role of omics technologies in refining these strategies. By bridging fundamental research and cultivation-based applications, such tools offer a gateway towards more sustainable and efficient in vitro cultivation systems, leading to a deeper understanding and potential manipulation of the plant holobiont.

Molecularly diverse lonazolac-inspired pyrazole-cyanopyridin-2-one conjugates: design, synthesis, in vitro, in vivo and in silico studies as multi-target anti-inflammatory agents - Marwa A. Aziz; Azizah M. Malebari; Tarek S. Ibrahim; Mohamed F. Radwan; Deiaa E. Elsayed Abouzed; Rasha M. Allam; Majed Alharbi; Ahdab N. Khayyat; Gamal El-Din A. Abuo-Rahma; Mamdouh F. A. Mohamed (Molecular Diversity, 2026)

Fennel essential oil as a natural feed additive to mitigate heat stress in broilers: Effects on growth, physiological and immunological responses, and intestinal morphology - Samar A. Tolba; Shimaa A. Amer; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Gehad E. Elshopakey; Noura A. Abd-Allah; Rehab Reda; Rehab I. Hamed; Gehan K. Saleh; Gehan N. Alagmy; Simon J. Davies; et al. (Journal of Thermal Biology, 2026)

How operational strategies influence nitrogen removal and nitrous oxide emissions: Insights from a full-scale wastewater treatment plant - Mostafa Khalil; Marwan Alsaleh; Ahmed Elsayed; Hussein Aqeel; Ahmed Al-Omari; Shannon Cavanaugh; Farokh Laqa Kakar; Katherine Bell; Allegra K. da Silva; Jose Porro; Ahmed AlSayed; Steven N. Liss; et al. (Journal of Environmental Management, 2026)

Evaluation of lactoferrin administration as an antibiotic alternative growth promoter: impacts on rabbit’s growth, meat quality, blood biochemical parameters, immune status, antioxidant status, and tissue histology - Tharwat A. Imbabi; Shimaa A. Amer; Eman H. Halawa; Islam I. Sabeq; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Shimaa N. Edris; Simon J. Davies; Lamiaa M. El-Maghraby; Abdalla El-Hadary; Ebrahim Elkhtab; Mohamed H. Abdel Aal; et al. (Tropical Animal Health and Production, 2025)

Microbial shifts and VFA production in the optimization of anaerobic digestion by thermal hydrolysis coupled with vacuum fermentation - Farokh Laqa Kakar; Hussain Aqeel; Frances Okoye; Elsayed Elbeshbishy; Steven N. Liss (Bioresource Technology, 2025)

Metabolite Profiling of Alectryon Tomentosus Leaf Extract via GC/MS Analysis and Its Renal Protective Effect - Salma A. El Sawi; Elsayed A. Aboutabl; Khaled N. Rashed; Amany A. Sleem; Nermin A. Ragab (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2025)

Mitigating potential of Malva parviflora leaves against Polyram DF (dry flowable) toxicity in Nile tilapia: immune/apoptotic markers, biochemical, antioxidant, and histopathological insights - Elsayed M. Younis; Rowida E. Ibrahim; Abdelwahab A. Abdelwarith; Engy Mohamed Mohamed Yassin; Kholoud A. Alhallag; Mohammed S. Sobh; Mohamed Shaalan; Tarek Khamis; Afaf N. Abdel Rahman (Fish Physiology and Biochemistry, 2025)

New trends in mycosynthesis of cellulose nanocrystals promoted by gamma irradiation of sugarcane bagasse - R. S. Abdelkader; G. A. Helal; Y. G. M. Galal; S. M. Soliman; R. R. Khalil; N. Elsayed (International Journal of Environmental Science and Technology, 2025)
The biological synthesis of cellulose nanocrystals (CNCs) involves utilizing cellulose-degrading microorganisms or their hydrolytic enzymes as catalysts for the controlled degradation of cellulose, yielding CNCs. Chemical synthesis of CNCs involves acid hydrolysis conducted for 45 min at 45 °C using sulfuric acid (64%). Neurospora intermedia (Assiut University Mycological Center (AUMC) 14,359), Fusarium verticillioides (AUMC 14360), and Rhizopus oryzae (AUMC 14361) were employed in the preparation of CNCs. Before both chemical and biological treatments, sugarcane bagasse (SCB) was irradiated with doses of 100, 200, and 300 kGy, enhancing the yield of nanocellulose from the cellulosic feedstock. The resultant nanocellulose was initially assessed using UV–Vis spectroscopy, and the characterization was further refined through Dynamic Light Scattering analysis to delineate particle size distribution within the nanoscale and to evaluate stability. CNCs and chemically purified cellulose (CPC) displayed analogous Fourier Transform Infrared Spectroscopy but were markedly different from SCB. X-ray Diffraction patterns revealed a notably higher crystallinity of cellulose in nanocellulose, with larger crystallite dimensions compared to CPC and SCB. Transmission Electron Microscope investigations elucidated the morphology of the synthesized nanoparticles. In summary, the selection of F. verticillioides for nanocellulose production represents a promising and sustainable approach that combines effectiveness, environmental friendliness, and cost-efficiency in the synthesis of this valuable nanomaterial. Graphical abstract

Ameliorative potential of Populus alba leaf powder against hexaflumuron exposure in Nile tilapia: immune-antioxidant, biochemical, histological, and transcriptomic analysis - Rowida E. Ibrahim; Mohamed F. M. Farag; Mohammed S. Sobh; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Shefaa M. Bazeed; Aya Elgamal; Tarek Khamis; Simon J. Davies; Afaf N. Abdel Rahman (Fish Physiology and Biochemistry, 2025)

Dietary Prunus armeniaca augments antioxidant-immune-capacity, absorptive function, and growth and upregulates nutrient transporters and immune-regulatory genes of Oreochromis niloticus - Afaf N. Abdel Rahman; Sara T. Elazab; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquaculture, 2025)

Retraction notice to “The anti-parasitic effect of Melaleuca alternifolia oil against gills monogeneans (Dactylogyrus spp) infestation of Clarias gariepinus: Hematology, immune response, and histopathological/immunohistochemical investigation of gills” [Aquaculture 584 (2024) 740639] - Afaf N. Abdel Rahman; Mohamed F.M. Farag; Alshimaa A. Khalil; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Shimaa R. Masoud; Shefaa M. Bazeed; Aya Elgamal; Refaat Ras; Simon J. Davies; Rowida E. Ibrahim; Amany M. Abd El-Ghany (Aquaculture, 2025)

Lead toxicity in African catfish: Promising role of magnetite nanogel against etho-neurological alterations, antioxidant suppression, gene toxicity, and histopathological/ immunohistochemical disruptions - Afaf N. Abdel Rahman; Heba H. Mahboub; Rasha M.M. Ezz-Eldin; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Tarek Khamis; Enas K. Aziz; Walaa A.A. Basha; Ibrahim Elmaghraby; Simon J. Davies; Sameh H. Ismail; Yasmin A. Reyad (Aquaculture, 2025)

Expression profiling of antimicrobial peptides and immune-related genes in Nile tilapia following Pseudomonas putida infection and nano-titanium dioxide gel exposure - Heba H. Mahboub; Morteza Yousefi; Hosny Ahmed Abdelgawad; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Emad Sakr; Tarek Khamis; Sameh H. Ismail; Afaf N. Abdel Rahman (Fish & Shellfish Immunology, 2025)

Antagonistic effects of Bacillus subtilis-derived chitosan nanoparticles on growth performance, stress biomarkers, and histological alterations of cadmium-intoxicated Nile tilapia fingerlings - Mohsen Abdel-Tawwab; Elsayed A. Eldessouki; Hoda A. Abd-Ellatieff; Riad H. Khalil; Nasser M. El-Sabbagh; Hamida M. Saleh; Nehad A. Saleh; Taghrid M. N. Abdelhakim; Dalia H. Samak (Aquaculture International, 2024)
Heavy metals including cadmium (Cd) are one of the major persistent and non-biodegradable wastewater pollutants. However, Cd reaches the aquatic ecosystem via industrial and agricultural waste discharges and causes serious deterioration in the welfare status of aquatic animals. The use of feed supplements with immune-stimulants to mitigate the toxic influences of heavy metals including Cd is a much more intriguing point. Thus, the current experiment used the bio-synthetized chitosan nanoparticles derived from Bacillus subtilis (Bs-CNPs) as a feed supplement and evaluated its ameliorative impacts on the growth and welfare status of Cd-intoxicated Nile tilapia ( Oreochromis niloticus ). Bifactorial design (3 Bs-CNPs levels × 3 Cd levels) was used in the current study where Nile tilapia fingerlings (58–63 g) were fed on 0.0, 2, and 4 g Bs-CNPs/kg feed alongside with exposing to 0.0, 0.392, and 0.784 mg Cd/L for 60 days to represent nine treatments as follows: T1: control group (no Cd exposure; no Bs-CNPs supplement); T2 and T3: fish were intoxicated with 0.784 and 0.392 mg Cd/L, respectively; T4 and T5: fish fed on 2 and 4 g Bs-CNPs/kg feed, respectively; T6 and T7: fish were fed on 2 g Bs-CNPs/kg feed along with exposure to 0.784 and 0.392 mg Cd/L, respectively; and T8 and T9: fish were fed on 4 g Bs-CNPs/kg feed along with exposure to 0.784 and 0.392 mg Cd/L, respectively. It is noted that the Cd-intoxicated fish exhibited significant retardation in growth performance and digestive enzyme activities with a decline in their survival rate compared to the control group (T1). The results also revealed that exposing fish to Cd toxicity alone with no feed supplement (T2 and T3) experienced abnormal clinical signs and behavioral changes. Compared with the control group (no Cd with no Bs-CNPs), highest values of cortisol, glucose, aspartate and alanine aminotransferase, and acetylcholine esterase activity were found in fish fed on the control diet along with exposure to 0.784 mg Cd/L. Higher Cd restudies in liver, intestine, gills, kidney, and muscles tissues were detected in fish exposed to 0.784 mg Cd/L alone and the sequence order of Cd levels in different fish organs is intestine > gills > liver > kidney > muscles. Remarkable pathological alterations in hepatic and intestinal tissues were also observed. On the other hand, feeding Nile tilapia on Bs-CNPs-enriched diets alone with no Cd exposure enhanced their growth performance, digestive enzyme activities, and hematological parameters with no Cd residues in fish organs. Interestingly, feeding the Cd-intoxicated fish on diets with Bs-CNPs (4 g/kg feed) returned their growth, digestive enzymes, hematological, and biochemical parameters to approximate those of the control group. Furthermore, these treatments showed histopathological alteration recovery in the intestine and liver tissues is similar to those in the control group (no Cd with no Bs-CNPs). Fish fed on Bs-CNPs levels with no Cd exposure showed no Cd residues in different fish organs. The Cd levels in different organs of fish exposed to 0.392 mg Cd/L along with feeding on Bs-CNPs (4 g/kg feed) were lower than those in Cd-exposed fish treatments. Consequently, the current study evoked that feeding Nile tilapia fingerlings on Bs-CNPs (4 g/kg feed) could enhance their growth performance and protect the fish from the Cd toxicity that may occur in the aquatic ecosystem.

Using moringa (Moringa oleifera) seed protein hydrolysate as a dietary protein supplement modulates hemato-biochemical indices, antioxidant response, and tissue histo-morphology of Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Shimaa A. Amer; Nasreddin R. Rhouma; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Heba M. Abdel-Ghany; Gehad E. Elshobaky; Mahmoud M. El-Saber; Ali Osman; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture International, 2024)

Efficacy of the dietary Malva parviflora leaves in modulating immune-antioxidant functions, resistance to Candida albicans and Streptococcus agalactiae infection, digestive/absorptive capacity, and growth of Nile tilapia (Oreochromis niloticus) - Afaf N. Abdel Rahman; Yasmin A. Reyad; Gehad E. Elshopakey; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Nehal Abd EL-Mageed; Afaf A. Kishta; Asmaa Yaseen; Simon J. Davies; Rowida E. Ibrahim (Aquaculture International, 2024)

Hexaflumuron insecticide exposure induces behavior alterations, hemato-biochemical disorders, antioxidant-immune dysfunction, and histopathological alterations in Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Moustafa M. S. Fouda; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Eman Wagih; Basma A. Elshafey; Simon J. Davies; Afaf N. Abdel Rahman (Veterinary Research Communications, 2024)

The Combination Between Super Absorbent Polymers (SAPs) and Biofertilizers Could be an Ecofriendly Approach for Soil Chemical Properties Improving and Sustainable Wheat (Triticum Sativum) Production in Sandy Loam Soil - Osama I. A. Negim; Moustafa H. A. Moharam; Elsayed F. Elsayed; Fatma N. Thabit (Journal of Soil Science and Plant Nutrition, 2024)
Sustainable agriculture aims to provide food needs while improving soil health and protecting it from degradation and contamination from excessive chemical fertilizer use. Sandy-textured soils have low fertility and water-holding capacity. This study assessed the integrated impact of super absorbent polymers (SAPs) and biofertilizer application on the soil chemical characteristics and wheat growth parameters in sandy loam soil. Two super absorbent polymers (SAPs) included Barbary plant G3 (P1) and Aqua Gool polymer (P2), and four microbial inoculations ( Trichoderma harzianum (T), Actinomycetes ( Streptomyces rochei and Streptomyces atrovirens) (AC1 and AC2), and Bacillus subtilis (B)) as biofertilizers were used in our pot experiment. The SAPs were applied to soil at a level of 0.2% (w/w), while biofertilizers were applied in the form of microbial cell suspensions (50 ml per pot) in addition to treating wheat seed with these suspensions during cultivation. Wheat plants were irrigated every 8 days to field capacity level. Amending soil with super absorbent polymers and microbes either individually or in combination significantly reduced pH and EC, increased organic matter level, and the availability of macro- and micronutrients in soil. Wheat growth metrics, including shoot length, tiller number, biomass accumulation, leaf area, and grain yield, exhibited considerable enhancements relative to the plants of the control treatment. The interaction between P1 polymer and Streptomyces atrovirens (AC2) showed the highest performance in improving the almost studied parameters. The application of SAPs with microbial biofertilizers offers a promising eco-friendly method for enhancing soil health and wheat yield.

Synthesis and characterization of Turbinaria ornata mediated Zn/ZnO green nanoparticles as potential antioxidant and anti-diabetic agent of enhanced activity - Amira S. Diab; Khaled N. M. Elsayed; Ahmed M. El-Sherbeeny; Wail Al Zoubi; Stefano Bellucci; Mostafa R. Abukhadra (Frontiers in Marine Science, 2024)
Turbinaria ornata marine macro-algae (TUN) have been applied as carriers for the metallic zinc/ZnO blended nanoparticles, which were synthesized by implementing the extracted phytochemicals of the algae. The resulting hybrid bio-composite (Zn@ZnO/TUN) was characterized as a potential product of promising antioxidant and antidiabetic characteristics in synergetic studies. The obtained composite demonstrate t6he existing or complex biological active groups related to zinc (Zn-O stretching and tetrahedral Zn coordination) and organic groups (amino, methyl, carboxylic, alkynes, P=O, C–C–O, C=N, and N–O) corresponding to the extracted phytochemicals of algae (polysaccharides, phospholipids, lipids, fucose, and phosphodiester). The assessment of Zn@ZnO/TUN hybrid as an anti-oxidant agent validated excellent effectiveness towards the commonly examined radicals (DPPH (88.2 ± 1.44%), nitric oxide (92.7 ± 1.71%), ABTS (90.5 ± 1.8%), and O 2 ●− (30.6 ± 1.32%), considering the determined performance for the commercially used standard (ascorbic acid). Regarding the antidiabetic properties, the incorporation of Zn@ZnO/TUN inhibits the function and activities of the key oxidizing enzymes, either the commercial forms (α-amylase (88.7 ± 1.3%), α-glucosidase (98.4 ± 1.3%), and amyloglucosidase (97.3 ± 1.4%) or the crude intestinal active forms (α-amylase (66.2 ± 1.4%) and α-glucosidase (95.1 ± 1.5%). This inhibitory effectiveness of Zn@ZnO/TUN is significantly better than the measured performances using commercialized miglitol drugs and slightly better than acarbose. Considering the expense and adverse effects of conventional medications, the synthesized Zn@ZnO/TUN blend could be evaluated as a marketable antidiabetic and antioxidant medication. The findings also demonstrate the influence of the derived phytochemicals from Turbinaria ornata and the incorporation of its algae residuals as carriers for the metal nanoparticles on the biological function of the composite. The cytotoxicity investigation reflected safety effect of the composite on colorectal fibroblast cells (CCD-18Co) (96.3% cell viability) and inhibition effect on cancerous colorectal cells (HCT-116) (47.3% cell viability).

Effects of dietary Hyphaene thebaica powder on reproductive performance, physiological parameters, growth, and disease resistance in Clarias gariepinus - Alshimaa A. Khalil; Shimaa A. Amer; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture International, 2024)

Retraction Note: In vitro antioxidant, anticancer, anti-inflammatory, anti-diabetic and anti-Alzheimer potentials of innovative macroalgae bio-capped silver nanoparticles - Manal N. Abdel Azeem; Osama M. Ahmed; Mohamed Shaban; Khaled N. M. Elsayed (Environmental Science and Pollution Research, 2024)

Durable graphene-based alkyd nanocomposites for surface coating applications - Mohamed S. Selim; Abdelaziz N. El-hoshoudy; ElSayed G. Zaki; Ashraf M. EL-Saeed; Ahmed A. Farag (Environmental Science and Pollution Research, 2024)
Recently, the scientific community’s main goal is the long-term sustainability. Vegetable oils are easily accessible, non-depletable, and cost-effective materials. Vegetable oils are used to prepare polymeric alkyd surfaces. Novel and exciting designs of alkyd/graphene nanocomposites have provided eco-friendly thermal stability and protective coating surfaces. This review has briefly described important graphene-based alkyd nanocomposites along with their applications as protective coatings. These alkyd composites have high hydrophobicity, corrosion resistance, and durability. Graphene-based alkyd nanocoatings have many industrial and research interests because of their exceptional thermal and chemical properties. This work introduces an advanced horizon for developing protective nanocomposite coatings. The anti-corrosion properties and coatings’ longevity may be improved by combining the synergistic effects of hybrid nanofillers introduced in this work.

Adsorption and antibacterial studies of a novel hydrogel adsorbent based on ternary eco-polymers doped with sulfonated graphene oxide developed from upcycled plastic waste - Marwa H. Gouda; M.M. Khowdiary; Hind Alsnani; N. Roushdy; M. Elsayed Youssef; Mohamed Elnouby; Noha A. Elessawy (Journal of Contaminant Hydrology, 2024)

Retracted: The anti-parasitic effect of Melaleuca alternifolia oil against gills monogeneans (Dactylogyrus spp) infestation of Clarias gariepinus: Hematology, immune response, and histopathological / immunohistochemical investigation of gills - Afaf N. Abdel Rahman; Mohamed F.M. Farag; Alshimaa A. Khalil; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Shimaa R. Masoud; Shefaa M. Bazeed; Aya Elgamal; Refaat Ras; Simon J. Davies; Rowida E. Ibrahim; Amany M. Abd El-Ghany (Aquaculture, 2024)

Pharmacodynamic Studies of Pravastatin Sodium Nanoemulsion Loaded Transdermal Patch for Treatment of Hyperlipidemia - Seham I Elsayed; Marwa S El-Dahan; Germeen N. S Girgis (AAPS PharmSciTech, 2024)
Pravastatin sodium (PVS) is a hypolipidemic drug with poor oral bioavailability due to the first-pass effect. Therefore, this study aims to formulate and evaluate transdermal patches containing PVS-loaded nanoemulsions (PVS-NEs) to increase PVS’s hypolipidemic and hepatoprotective activities. PVS-NEs were prepared using the aqueous titration method, where oleic acid was chosen as an oil phase, and span 80 and tween 80 were used as surfactant and cosurfactant respectively. Droplet size (DS), polydispersity index (PDI), zeta potential (ZP), clarity, and thermodynamic stability of NEs were all characterized. Also, PVS-NEs (NE2) with 50% oil phase, 40% SC mix 2:1, and 10% water were selected as an optimum formula based on the results of DS (251 ± 16), PDI (0.4 ± 0.16), and ZP (-70 ± 10.4) to be incorporated into a transdermal patch, and PVS-NE2 loaded transdermal patches (PVS-NE2-TDPs) were prepared by solvent evaporation method. F1 patch with HPMC E15 and PVP K30 in a ratio of 3:1 represented satisfactory patch properties with good drug-excipients compatibility. Thus, it was selected as an optimum patch formula. The optimized F1 patch was characterized for thickness, moisture content, weight variation, and drug-excipients incompatibility. Therefore, it was subjected to ex vivo skin permeation and finally pharmacodynamic studies. Ex vivo permeation studies of F1 revealed that the cumulative amount of PVS permeated across rat skin was 271.66 ± 19 µg/cm 2 in 72 h, and the pharmacodynamic studies demonstrated that the F1 patch was more effective in treating hyperlipidemia than PVS-TDP (control patch) based on both blood analysis and histopathological examination. Graphical Abstract

Di (2-ethylhexyl) phthalate alters neurobehavioral responses and oxidative status, architecture, and GFAP and BDNF signaling in juvenile rat's brain: Protective role of Coenzyme10 - Naglaa Z.H. Eleiwa; Alaa S.F. Elsayed; Enas N. Said; Mohamed M.M. Metwally; Yasmina M. Abd-Elhakim (Food and Chemical Toxicology, 2024)

Irrigation Water Management in a Water-Scarce Environment in the Context of Climate Change - Mohamed Elsayed Gabr; Ahmed Awad; Hesham N. Farres (Water, Air, & Soil Pollution, 2024)
Climate change has a considerable impact on irrigated agriculture, which is vital for food and fiber production. In this study, in the context of climate change, simulation model CROPWAT 8 was employed to compute the reference evapotranspiration, and net irrigation water requirement for wheat, barley, maize, sugar beet, potato, tomato, and date palm. In addition, the WaterGEMS model was utilized to design a new sprinkler irrigation system to run long-term simulations of hydraulic behavior within pressurized pipe networks to irrigate 43 acres for two arid sites (Siwa Oasis and West Elminya fields) inside the 1.5-million-acre groundwater irrigation project in the Egyptian western desert. Five scenarios for climate change were employed in the current (1991–2023), representative concentration path (RCP) 8.5 greenhouse gas emission scenarios for the 2040s, 2060s, 2080s, and 2100s. Mean ET o values for the current scenario show 4.56 and 5.7 mm for the Siwa Oasis and West Elminya fields, respectively. The climate changes cause an increase of the reference evapotranspiration by 4.6, 5.9, 9.4, and 12.7% for RCP: 8.5 greenhouse gas emissions for the 2040s, 2060s, 2080s, and 2100s scenarios, respectively, for the Siwa Oasis field. On the other hand, an increased ratio for the reference evapotranspiration by 4.2, 5.4, 8.6, and 11.6% was observed for the scenarios in the West Elminya field, respectively. The designed sprinkler system indicated a capacity of 111.4 m 3 h −1 and 167 m 3 h −1 for Siwa and West Elminya fields, respectively. The study suggests using crop patterns for wheat, barley, potato, and sugar beet to save irrigation water. Graphical abstract

Use of moringa protein hydrolysate as a fishmeal replacer in diet of Oreochromis niloticus: Effects on growth, digestive enzymes, protein transporters and immune status - Shimaa A. Amer; Afaf N. Abdel Rahman; Mohamed ElHady; Ali Osman; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Amr A. Moustafa; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquaculture, 2024)

The anti-bacterial efficacy of zinc oxide nanoparticles synthesized by Nelumbo nucifera leaves against Clostridium perfringes challenge in Oreochromis niloticus - Rowida E. Ibrahim; Moustafa M.S. Fouda; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Gamal A. Salem; Ahmed Asaid Elkady; Sameh H. Ismail; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture, 2024)

Nelumbo nucifera synthesized selenium nanoparticles modulate the immune-antioxidants, biochemical indices, and pro/anti-inflammatory cytokines pathways in Oreochromis niloticus infected with Aeromonas veronii - Rowida E. Ibrahim; Gehad Elshobaky; Mohamed ElHady; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Nasreddin R. Rhouma; Suzan K. Murad; Engy Mohamed Mohamed Yassin; Tarek Khamis; Sameh H. Ismail; Simon J. Davies; Afaf N. Abdel Rahman (Fish & Shellfish Immunology, 2024)

Potential role of dietary Boswellia serrata resin against mancozeb fungicide-induced immune-antioxidant suppression, histopathological alterations, and genotoxicity in Nile tilapia, Oreochromis niloticus - Afaf N. Abdel Rahman; Dalia E. Altohamy; Gehad E. Elshopakey; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Nora M. Elseddawy; Aya Elgamal; Shefaa M. Bazeed; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquatic Toxicology, 2023)

Narcissus pseudonarcissus L. (Amaryllidaceae) bulb metabolite profiling and biological activities - Youstina Refaat Boshra; Eman Zekry Attia; Ahmed G. Darwish; Maria Refaat Boshra; Mohamed N. Amin; Ashraf Nageeb Elsayed Hamed; Samar Yehia Desoukey; John Refaat Fahim (South African Journal of Botany, 2023)

Neem seed protein hydrolysate as a fishmeal substitute in Nile tilapia: Effects on antioxidant/immune pathway, growth, amino acid transporters-related gene expression, and Aeromonas veronii resistance - Afaf N. Abdel Rahman; Shimaa A. Amer; Shimaa R. Masoud; Mahmoud M. El-Saber; Ali Osman; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Simon J. Davies; Tarek Khamis; Rowida E. Ibrahim (Aquaculture, 2023)

Acute mancozeb-fungicide exposure induces neuro-ethology disruption, health disorders, and immune-oxidative dysfunction in Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Mohamed A. Elbealy; Gamal A. Salem; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Eman Wagih; Ahmed Asaid Elkady; Simon J. Davies; Afaf N. Abdel Rahman (Aquatic Toxicology, 2023)

Comparative Study on Ginger Powder and Ginger Extract Nanoparticles: Effects on Growth, Immune–Antioxidant Status, Tissue Histoarchitecture, and Resistance to Aeromonas hydrophila and Pseudomonas putida Infection in Oreochromis niloticus - Shaimaa A. A. Ahmed; Abdelhakeem El-Murr; Yasser Abd Elhakim; Mohamed M. Metwally; Amany Abd El Aziz Gharib; Shimaa A. Amer; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Simon J. Davies; Enas N. M. Khalil (Fishes, 2023)
A 10 week feeding trial was conducted to evaluate the potential effects of ginger powder (GP) and ginger extract nanoparticles (GNPs) on the growth parameters, digestive enzymes (lipase and amylase) activities, blood hematology, blood biochemical indices, immune indices (interleukin 10, immunoglobulin M, nitric oxide, and lysozymes), antioxidant activity, histological characteristics of kidney, spleen, liver, and intestine, and resistance to Aeromonas hydrophila or Pseudomonas putida infection in Nile tilapia, Oreochromis niloticus. Fish (n = 225, 27.01 ± 0.15 g) were stocked in 15 glass tanks (50 × 40 × 60 cm) and randomly allocated to five experimental treatments (TRTs) in triplicate (15 fish/replicate, 45 fish/TRT), consisting of five isocaloric–isonitrogenous diets. The treatments comprised the basal diet (1) without any additives (control group, CON), (2) with 0.5% GP (GP0.5), (3) with 1% GP (GP1), (4) with 0.5% GNPs (GNPs0.5), and (5) with 1% GNPs (GNPs1). Fish were manually fed to satiety three times a day (at 9 a.m., 12 p.m., and 2 p.m.). Fish were weighed at the start of the experiment, then the body weight, weight gain, feed intake, and feed conversion ratio were determined at the end of the experiment. At the end of the feeding period, 15 fish/TRT were intraperitoneally inoculated with two pathogenic bacterial strains (A. hydrophila or P. putida) in two separate challenge tests. Blood samples were collected from each TRT at two aliquots for hematological and biochemical analysis at the end of the feeding period. A significant improvement in fish growth was observed in GP and GNPs TRTs compared to the control group. There were no significant changes in the total amount of feed intake/fish in response to the experimental diets. Diets enriched with GNPs, particularly the GNPs1 TRT, resulted in a significant increase (p

Impact of Streptococcus agalactiae Challenge on Immune Response, Antioxidant Status and Hepatorenal Indices of Nile Tilapia: The Palliative Role of Chitosan White Poplar Nanocapsule - Afaf N. Abdel Rahman; Sameh H. Ismail; Moustafa M. S. Fouda; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Samah S. Khalil; Mahmoud M. El-Saber; Ahmed E. Abdelhamid; Simon J. Davies; Rowida E. Ibrahim (Fishes, 2023)
A new insight into the synthesis of the herbal plant (White poplar, Poplus alba) leave extract using chitosan nanocapsule was studied. The in vitro antibacterial activity of chitosan white poplar nanocapsule (CWPNC) against Streptococcus agalactiae (S. agalactiae) was determined. About 120 fish were categorized for 7 days into four groups. The first and second (CWPNC) groups were treated with 0 mg/L and 3 mg/L CWPNC in the water, respectively, without being challenged; the first group was a control. The third (S. agalactiae) and fourth (CWPNC + S. agalactiae) groups were treated with 0 and 3 mg/L CWPNC, respectively, and challenged with S. agalactiae (0.5 × 107 CFU/mL). The obtained results revealed that CWPNC had an in vitro antibacterial activity against S. agalactiae. Moreover, S. agalactiae infection caused a significant elevation (p

Effectiveness of Sacrificial Shielding for Blast Mitigation of Steel Floating Pontoons - Yasser A. Khalifa; Mohamed N. Lotfy; Elsayed Fathallah (Journal of Marine Science and Engineering, 2023)
Floating pontoons have played a supreme and indispensable role in crises and disasters for both civil and military purposes. Floating bridges and ferries are exposed to blast loadings in the case of wars or terrorist attacks. The protection effectiveness of sacrificial cladding subjected to a blast was numerically investigated. In this study, a steel ferry has been simulated and exposed to side explosions with different explosive charges at certain stand-off distances, according to military standards from NATO and American standard TM5. In this simulation, nonlinear three-dimensional hydro-code numerical simulation ANSYS autodyn-3d has been used. The results reported that the ferry could withstand a charge of 5 kg TNT at a stand-off distance of 1 m without failure. The main objective of this research is to achieve a design that would increase the capacity against the blast loading with minimal plastic deformation in the absence of any failure in the ferry. Therefore, an innovative mitigation system has been proposed to dissipate the blast energy of the explosion based on the scientific theory of impedance using sacrificial cladding. The new mitigation system used a specific structural system in order to install the existing pontoon structure without any distraction. The response, elastic deformations, plastic deformations and plastic failure of the ferry were illustrated in this paper. Furthermore, the results revealed that the proposed mitigation system could mitigate more than 50% of the blast waves. The new design revealed promising results, which makes it suitable for mitigating blast waves. Finally, the results were provided with a reference for the preliminary design and application of sacrificial cladding for structural protection against blast waves.

In vitro assessment of antimicrobial, anti-inflammatory, and schistolarvicidal activity of macroalgae-based gold nanoparticles - Marwa Kamal; Neveen Abdel-Raouf; Hana Sonbol; Heba Abdel-Tawab; Mohamed Sayed Abdelhameed; Ola Hammouda; Khaled N. M. Elsayed (Frontiers in Marine Science, 2022)
There is a growing need to improve facile, eco-friendly, and cheap approaches for nanoparticle (NP) synthesis. Green protocols have been investigated for the fabrication of NPs using several natural sources as plants, algae, fungi, and bacteria. Thus, the present study proposed a rapid, convenient, and efficient biosynthesis of gold NPs (Au-NPs) using the ethanolic extracts of three macroalgae, i.e., Cystoseira myrica, C. trinodis , and Caulerpa prolifera . The reduction of Au ions and the fabrication of Au-NPs were validated using ultraviolet-visible (UV–Vis) spectroscopy, X-ray diffraction, Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), and zeta potential analysis. The produced Au-NPs were tested for their antibacterial, antifungal, anti-inflammatory, and schistolarvicidal activity. Results revealed the formation of Au-NPs with an average size of 12.6–15.5 nm and different shapes that are mainly spherical with pure crystalline nature. The strong antibacterial activities of C. trinodis – and C. myrica –based Au-NPs against E. coli (inhibition zones of 22 and 19 mm) and against Staphylococcus aureus (inhibition zones of 18 and 20.5 and mm) were recorded, respectively. On the other hand, the high antifungal activity of C. trinodis Au-NPs against Aspergillus niger and Alternaria alternate showed the inhibition zones of 18 and 17 mm, respectively. The high antifungal activity of C. trinodis Au-NPs against Candida albicans (inhibition zone 16 mm) was also recorded. Regarding anti-inflammatory and schistolarvicidal activity, Au-NPs fabricated using C. myrica showed 64.2% of the inhibitory effect on protein denaturation and recorded the highest schistolarvicidal activity against Schistosoma mansoni cercariae that sank and died after 7 min. Overall, these findings proved that macroalgal ethanolic extracts can be effectively used for the biosynthesis of Au-NPs. These Au-NPs offer a significant alternative antimicrobial, anti-inflammatory, and schistolarvicidal agents. for biomedical uses.

RETRACTED ARTICLE: In vitro antioxidant, anticancer, anti-inflammatory, anti-diabetic and anti-Alzheimer potentials of innovative macroalgae bio-capped silver nanoparticles - Manal N. Abdel Azeem; Osama M. Ahmed; Mohamed Shaban; Khaled N. M. Elsayed (Environmental Science and Pollution Research, 2022)
The antagonistic side effects of chemical medications led to the search for safe strategies such as biogenic agents. Correspondingly, this study aims to create biogenic, appropriate, auspicious and innovative therapeutic agents like Galaxaura elongata GE , Turbinaria ornata TO and Enteromorpha flexuosa EF macroalgae-based silver nanoparticles (Ag-NPs). The Ag + reduction and the creation of Ag[GE]-NPs, Ag[TO]-NPs and Ag[EF]-NPs have been validated using UV–visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM) and zeta potential analysis, and the chemical composition of macroalgae crude extracts was estimated through gas chromatography–mass spectrometry (GC–MS). Further, macroalgae-based Ag-NPs were tested for their free radical scavenging activity DPPH, ABTS, anticancer activity in human liver carcinoma (HepG2) cell line, distinctive inflammation forms and elevated α-amylase. Results showed that the biosynthesized Ag-NPs have unique mechanical and physicochemical characters attributed to their high relative surface area, nanosized dimensions and spherical shape. At dose of 200 µg/mL, the DPPH radical scavenging capacity was maximized with Ag[TO]-NPs (67.26%); however, Ag[EF]-NPs was the most potent as ABTs scavenger (97.74%). Additionally, Ag[GE]-NPs had the maximum proteinase inhibitory action with 59.78%. The 1000 µg/mL of Ag[GE]-NPs, Ag[TO]-NPs and Ag[EF]-NPs revealed significant inhibitions of cell growth of HepG2 resulting in cell viabilities 5.92%, 4.44% and 11.33%, respectively. These findings suggest that macroalgae bio-capped Ag-NPs have magnificent biological potentials for safe biomedical applications.

Model Synthetic Samples for Validation of NMR Signal Simulations - Nicholas N. A. Ling; Syed Rizwanullah Hussaini; Mahmoud Elsayed; Paul R. J. Connolly; Ammar El-Husseiny; Mohamed Mahmoud; Eric F. May; Michael L. Johns (Transport in Porous Media, 2022)
Simulations of nuclear magnetic resonance (NMR) signal from fluids contained in porous media (such as rock cores) need to account for both enhanced surface relaxation and the presence of internal magnetic field gradients due to magnetic susceptibility contrast between the rock matrix and the contained fluid phase. Such simulations are typically focussed on the extraction of the NMR T 2 relaxation distribution which can be related to pore size and indirectly to system permeability. Discrepancies between such NMR signal simulations on digital rock cores and associated experimental measurements are however frequently reported; these are generally attributed to spatial variations in rock matric composition resulting in heterogeneously distributed NMR surface relaxivities (ρ) and internal magnetic field gradients. To this end, a range of synthetic sediments composed of variable mixtures of quartz and garnet sands were studied. These two constituents were selected for the following reasons: they have different densities allowing for ready phase differentiation in 3D μCT images of samples to use as simulation lattices and they have distinctly different ρ and magnetic susceptibility values which allow for a rigorous test of NMR simulations. Here these 3D simulations were used to calculate the distribution of internal magnetic field gradients in the range of samples, these data were then compared against corresponding NMR experimental measurements. Agreement was reasonably good with the largest discrepancy being the simulation predicting weak internal gradients (in the vicinity of the quartz sand for mixed samples) which were not detected experimentally. The suite of 3D μCT images and associated experimental NMR measurements are all publicly available for the development and validation of NMR simulation efforts.

Soil Fabric and Transitional Behavior in Completely Decomposed Granite: An Example of Well-Graded Soil - Elsayed Elkamhawy; Huabin Wang; Tarek N. Salem; František Vranay; Martina Zelenakova (Journal of Marine Science and Engineering, 2021)
Unlike sedimentary soils, limited studies have dealt with completely decomposed granite (CDG) soils, even though they are plentiful and used extensively in several engineering applications. In this paper, a set of triaxial compression tests have been conducted on well-graded intact and disturbed CDG soils to study the impact of the fabric on soil behavior. The soil behavior was robustly affected by the soil fabric and its mineral composition. The intact soil showed multiple parallel compression lines, while a unique isotropic compression line was present in the case of disturbed soil. Both the intact and disturbed soils showed unique critical state lines (CSL) in both the e-log p′ and q-p′ spaces. The intact soil showed behavior unlike other transitional soils that have both distinct isotropic compression lines ICLs and CSLs. The gradient of the unique ICL of the disturbed soil was much more than that of the parallel compression lines of the intact soil. In the intact soil, the slope of the unique CSL (M) in the q-p′ space was higher than that of the disturbed soil. The isotropic response was present for both the intact and disturbed soils after erasing the inherited anisotropy as the stress increased with irrecoverable volumetric change. Soil fabric is considered the dominant factor in the transitional behavior and such a mode of soil behavior is no longer restricted to gap-graded soil as previously thought.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Embryonic thermal manipulation of Japanese quail: effects on embryonic development, hatchability, and post-hatch performance - Saad N. El-Shater; Hamdy Rizk; Hisham A. Abdelrahman; Mohamed A. Awad; Elsayed F. Khalifa; Karim M. Khalil (Tropical Animal Health and Production, 2021)

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Quantitative Tortuosity Measurements of Carbonate Rocks Using Pulsed Field Gradient NMR - Kaishuo Yang; Ming Li; Nicholas N. A. Ling; Eric F. May; Paul R. J. Connolly; Lionel Esteban; Michael B. Clennell; Mohamed Mahmoud; Ammar El-Husseiny; Abdulrauf R. Adebayo; Mahmoud Mohamed Elsayed; Michael L. Johns (Transport in Porous Media, 2019)

Method validation and evaluation of household processing on reduction of pesticide residues in tomato - Helmy Hassan; Elham Elsayed; Abd El-Rahman Abd El-Raouf; Salma N. Salman (Journal of Consumer Protection and Food Safety, 2019)

Sequencing and Utilization of the Gossypium Genomes - Andrew H. Paterson; Jun-kang Rong; Alan R. Gingle; Peng W. Chee; Elizabeth S. Dennis; Danny Llewellyn; Leon S. Dure; Candace Haigler; Gerald O. Myers; Daniel G. Peterson; Mehboob ur Rahman; Yusuf Zafar; et al. (Tropical Plant Biology, 2010)

Laboratory-based surveillance of patients with bacterial meningitis in Egypt (1998–2004) - S. Afifi; M. O. Wasfy; M. A. Azab; F. G. Youssef; G. Pimentel; T. W. Graham; H. Mansour; N. Elsayed; K. Earhart; R. Hajjeh; F. Mahoney (European Journal of Clinical Microbiology & Infectious Diseases, 2007)